Professional Education in the US: historical, legal and curricular landmarks - Deise Aparecida Peralta; Ana Lucia Braz Dias; Harryson Junio Lessa Gonçalves (Universidade Federal do Rio Grande do Sul, 2018)
ABSTRACT: This article, based on data compiled in a comparative study, outlines the USA education system, followed by a description of historical milestones and the main legislation that defines professional education in that country. Without pretension to carry out systematic analyzes, the article is based on the perception in its authors constructed from visits, interviews, conversations, reading of legislation and contact with a culture of American reference information for professional performance. A configuration of professional education in that country illustrates a force that moves it. There is also a strong movement to pass legislation covering large-scale Member States to monitor student performance.